The evolution of a submarine landform record following recent and multiple surges of Tunabreen glacier, Svalbard. (15th January 2015) - Flink, Anne Elina; Noormets, Riko; Kirchner, Nina; Benn, Douglas I.; Luckman, Adrian; Lovell, Harold
Abstract: This study focuses on the glacial landform record associated with recent surge events of Tunabreen – a calving tidewater glacier in Tempelfjorden, Spitsbergen. Submarine geomorphology and recent terminal fluctuations of Tunabreen's glacier front were studied using high-resolution multibeam-bathymetric data and a range of published and remote-sensing sources, including topographic maps, satellite images and aerial photographs. The retreat moraines in the inner part of Tempelfjorden have been correlated with glacier terminus positions during retreat from the 2004 surge maximum. Glacier surface velocity and ice-front positions derived from high-resolution TerraSAR-X satellite data show ice movements at the glacier front during minor advances of the front in winter when calving is suppressed. This suggests that the moraines have formed annually during quiescent phase winter advances. Tunabreen has experienced three surges since the Little Ice Age (LIA). This is in contrast with most Svalbard surging glaciers which have long quiescent phases and have typically only undergone one or two surges during this time. The landform record in Tempelfjorden is distinguished from previously studied glacier-surge landsystems by four, well-preserved sets of landform assemblages generated by the LIA advance and three subsequent surges, all of which partly modify earlier landform records. Based on the unique landform record in Tempelfjorden, a new conceptual landsystem model for frequently surging glaciers has been put forward improving our understanding of the dynamics of the surging glaciers and, most importantly, how they can be distinguished from the climatically-controlled glaciers in the geological record. Highlights: The dynamics of Tunabreen glacier have been reconstructed by a combination of data. The landform record in Tempelfjorden comprises of a multiple-surge landsystem. Landforms in inner Tempelfjorden can be directly linked to the observed 2004 surge. The retreat moraines have formed annually. Winter advances can be correlated to the formation of the annual retreat moraines.